French Theory and Media Studies: What Can Media Cultural Studies Learn from M. Foucault, P. Bourdieu and J.-P. Sartre? Француска теорија и медиумските студии: Што можат медиумските културни студии да научат од М. Фуко, П. Бурдје и Ж.-П. Сартр? - Volčič, Zala; Ruskovska, Rodna (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Zala Volčič | Зала Волчич Title (English): French Theory and Media Studies: What Can Media Cultural Studies Learn from M. Foucault, P. Bourdieu and J.-P. Sartre? Title (Macedonian): Француска теорија и медиумските студии: Што можат медиумските културни студии да научат од М. Фуко, П. Бурдје и Ж.-П. Сартр? Translated by (English to Macedonian): Rodna Ruskovska | Родна Русковска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 215-246 Page Count: 31 Citation (English): Zala Volčič, “French Theory and Media Studies: What Can Media Cultural Studies Learn from M. Foucault, P. Bourdieu and J.-P. Sartre?,” Identities: Journal for Politics, Gender and Culture, Vol. 5, No 1 (Winter 2006): 215-246. Citation (Macedonian): Зала Волчич, „Француска теорија и медиумските студии: Што можат медиумските културни студии да научат од М. Фуко, П. Бурдје и Ж.-П. Сартр?“, превод од англиски Родна Русковска, Идентитети: списание за политика, род и култура, т. 5, бр. 1 (зима 2006): 215-246.